The Role of Myeloid-Derived Suppressor Cells in Immune Ontogeny - Gantt, Soren; Gervassi, Ana; Jaspan, Heather; Horton, Helen (Frontiers in Immunology, 2014)
Myeloid derived suppressor cells (MDSC) are a heterogeneous population of granulocytic or monocytic cells that suppress innate as well as adaptive immune responses. In healthy adults, immature myeloid cells differentiate into macrophages, dendritic cells, and granulocytes in the bone marrow, and MDSC are rarely detected in peripheral blood. However, in certain pathologies, in particular malignancies and chronic infection, differentiation of these cells is altered resulting in accumulation of circulating suppressive myeloid cells. MDSC express suppressive factors such as arginase-1, reactive oxygen species, and inducible nitric oxide synthase, which have the ability to inhibit T cell proliferation and cytoxicity, induce the expansion of regulatory T cells, and block natural killer cell activation. It is increasingly recognized that MDSC alter the immune response to several cancers, and perhaps chronic viral infections, in clinically important ways. In this review, we outline the potential contribution of MDSC to the generation of feto-maternal tolerance and to the ineffective immune responses to many infections and vaccines observed in early post-natal life. Granulocytic MDSC are present in large numbers in pregnant women and in cord blood, and wane rapidly during infancy. Furthermore, cord blood MDSC suppress in vitro T cell and NK responses, suggesting that they may play a significant role in human immune ontogeny. However, there are currently no data that demonstrate in vivo effects of MDSC on feto-maternal tolerance or immune ontogeny. Studies are ongoing to evaluate the functional importance of MDSC, including their effects on control of infection and response to vaccination in infancy. Importantly, several pharmacologic interventions have the potential to reverse MDSC function. Understanding the role of MDSC in infant ontogeny and their mechanisms of action could lead to interventions that reduce mortality due to early-life infections.